Brevipalpus-transmitted Orchid Fleck Virus Infecting Three New Ornamental Hosts in Florida. Issue 1 (20th November 2021) - Fife, Austin; Carrillo, Daniel; Knox, Gary; Iriarte, Fanny; Dey, Kishore; Roy, Avijit; Ochoa, Ronald; Bauchan, Gary; Paret, Mathews; Martini, Xavier
Abstract: We describe the first detection of orchid fleck virus (OFV) infecting three unreported hosts: Liriope muscari, cv. 'Gigantea' (Decaisne) Bailey, Ophiopogon intermedius Don and Aspidistra elatior Blume (Asparagaceae: Nolinoidaea) in Leon and Alachua Counties, FL. The orchid-infecting subgroup (Orc) of OFV infects over 50 plant species belonging to the plant families Orchidaceae, Asparagaceae (Nolinoidaea), and causes citrus leprosis disease in Citrus (Rutaceae). The only known vectors of OFV-Orc are the flat mites, Brevipalpus californicus (Banks) sensu lato (Trombidiformes: Tenuipalpidae). Florida has various plants in the landscape which Brevipalpus spp. feed on, which are susceptible to infection by OFV-Orc. Chlorotic ringspots and flecking were seen affecting Liriopogons ( Liriope and Ophiopogon spp.) in Leon County, FL. Nearby A. elatior also appeared chlorotic. Local diagnostics returned negative for common plant pathogens, therefore new samples were sent to the Florida Department of Agriculture and Consumer Services (FDACS) and USDA-ARS for identification. Two orchid-infecting strains of OFV were detected via combinations of conventional RT-PCR, RT-qPCR, Sanger sequencing, and high-throughput sequencing (HTS). Amplicons shared 98% nucleotide identity with OFV-Orc1 and OFV-Orc2 RNA2 genome sequences available in NCBI GenBank. Coinfections were detected in each county, but single strains of OFV-Orc were detected in L. muscari (Alachua, OFV-Orc2) and A. elatior (Leon, OFV-Orc1). Three potential mite vectors were identified via cryo-scanning electron microscopy (Cryo-SEM): B. californicus sensu lato, B. obovatus Donnadieu, and B. confusus Baker. In conclusion, OFV orchid strains are present in northern Florida, representing a risk for susceptible plants in the southeastern United States.